The Impact of Fiscal Deficit on Long-term Nominal Interest Rate in Nepal - Pandit, Rajendra (NRB Economic Review, 2005)
Growth of debt stock, changes in the debt composition, ownership structure of government debt and movement of interest rate on debt have been observed since the very beginning in Nepal. Public debt issues have been more and more market oriented and secondary market activities for short-term securities have expanded in recent years. Presently, the amount of debt service payment which exerts pressure on government budget constitutes more than one fourth of the total government expenditure. The theoretical prediction about the relationship between interest rate and government debt is still a matter of controversy. Empirical evidence of other countries on the relationship between interest rate and public debt has become inconclusive. This paper examines the relationship between long-term nominal interest rate and budget deficit variables in Nepal. The study finds the evidence that there exists positive but insignificant relationship between long-term nominal interest rate of government securities and budget deficit variables.